2014
DOI: 10.1093/mnras/stu1586
|View full text |Cite
|
Sign up to set email alerts
|

Astrometric follow-up observations of directly imaged sub-stellar companions to young stars and brown dwarfs★

Abstract: The formation of massive planetary or brown dwarf companions at large projected separations from their host star is not yet well understood. In order to put constraints on formation scenarios we search for signatures in the orbit dynamics of the systems. We are specifically interested in the eccentricities and inclinations since those parameters might tell us about the dynamic history of the systems and where to look for additional low-mass sub-stellar companions. For this purpose we utilized VLT/NACO to take … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
79
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 99 publications
10
79
2
Order By: Relevance
“…Figure 5 shows the astrometric monitoring in the last ∼20 years, and GQ Lup B's orbital motion is evident. Our results are consistent with the trends derived by Ginski et al (2014), r D~-1.4 mas yr −1 and ΔPA∼+0°.16 yr −1 . Table 1 also lists our astrometric measurements.…”
Section: Magao Astrometry Of Gq Lup Bsupporting
confidence: 93%
“…Figure 5 shows the astrometric monitoring in the last ∼20 years, and GQ Lup B's orbital motion is evident. Our results are consistent with the trends derived by Ginski et al (2014), r D~-1.4 mas yr −1 and ΔPA∼+0°.16 yr −1 . Table 1 also lists our astrometric measurements.…”
Section: Magao Astrometry Of Gq Lup Bsupporting
confidence: 93%
“…Indeed, the models of Ginski et al (2014) and Schwarz et al (2016) do not exclude low eccentricity orbits as would be expected for a planet-like formation within a larger protoplanetary disk. The morphology of the GQ Lup A disk points against a scattering origin for the companion.…”
Section: Implications For Formation Scenariosmentioning
confidence: 95%
“…The projected separation of the companion from the primary star is 0 7 (Ginski et al 2014), and recent work by Schwarz et al (2016) favors orbits with high eccentricity and semimajor axes 100-185 au. Near-infrared spectroscopy by Seifahrt et al (2007) showed Paβ line emission (equivalent width, EW=−3.83±0.12 Å), though subsequent observations by Lavigne et al (2009) give a limit an order of magnitude lower for the same line (EW=−0.46±0.08 Å), possibly pointing to time variability of Paβ and ongoing disk accretion.…”
Section: The Gq Lup Systemmentioning
confidence: 97%
See 1 more Smart Citation
“…In principle, clues about their origin can be inferred from a comparative abundance analysis with their host stars (e.g., Konopacky et al 2013;Barman et al 2015), measurements of their occurrence rate over time, long-term monitoring of their orbits (e.g., Ginski et al 2014;Rameau et al 2016;Blunt et al 2017), the physical properties of their circumplanetary disks Kraus et al 2015;Stamatellos & Herczeg 2015), and constraints on their mass and semimajor axis distributions (Biller et al 2013;Brandt et al 2014;Reggiani et al 2016). Indeed, Bryan et al (2016) recently concluded that dynamical scattering is probably not the dominant origin of wide PMCs based on the lack of close-in scatterers, the low rate of close-in giant planets in the field, and early orbital constraints for wide PMCs.…”
Section: Introductionmentioning
confidence: 99%